EP391/#571 Utilization of indocyanine green fluorescence angiography for anastomotic perfusion assessment following bowel resection for gynecologic malignancies: a pan-Canadian survey. (4th December 2022) - Spenard, Elisabeth; Nguyen, Julie; Daisy Kosa, S.; May, Taymaa
Abstract : Objectives: Real-time intraoperative assessment of anastomotic perfusion with indocyanine green fluorescence angiography(ICG-FA) is an innovative technique that effectively evaluates perfusion of bowel anastomoses. Our objective was to capture national practice patterns, characterize facilitators and barriers to ICG-FA utilization for bowel perfusion assessment. Methods: A survey was developed with a focus group of key stakeholders and methodologist in the field and piloted in advance of distribution. The survey captured: basic socio-demographics, work history, facilitators and barriers to use ICG-FA for bowel perfusion assessment, and modalities for further education including peer-reviewed article, surgical video, national/international conference, local grand rounds, and practical training. On July 1, 2021, the survey was distributed to 81 gynecologic oncologists within the Society of Gynecologic Oncology of Canada. Results: The response rate was 75%(n=61), with respondents from all Canadian provinces. The majority identified as women(80%, n=48), and have been in practice for less than 10 years(55%, n=33). 78%(n=47) performed bowel resection and 46%(n=28) used ICG-FA for bowel anastomotic perfusion assessment. The three most reported barriers to integrating ICG-FA into routine clinical practice were lack of training(32%), lack of equipment(28%), and lack of knowledge(26%). Surgical videos were the highest ranked desired educational modality followed by national/international conferences and peer-reviewed articles. Conclusions: Targeted training across multiple educational modalities is needed to build knowledge around ICG-FA for bowel perfusion assessment among the Canadian gynecologic oncologic community, with surgical videos being the preferred educational modality. Funding for necessary equipment may facilitate the uptake of this tool. This represents a national practice improvement opportunity.